State Sovereignty and Humanitarian Assistance: Navigating the Tension in International Armed Conflicts - Puspoayu, Elisabeth Septin; Widagdo, Setyo; Kusumaningrum, Adi; Kurniaty, Rika (Universitas Negeri Semarang, 2024)
This paper critically examines the intersection of state sovereignty and the provision of humanitarian assistance in the context of international armed conflicts, addressing a pressing and increasingly relevant issue in global legal discourse. While state sovereignty remains a cornerstone of international law, its application during armed conflict, especially regarding external humanitarian aid, raises complex questions of responsibility and intervention. Using a blend of primary and secondary legal sources, the study explores how sovereignty intersects with the state's obligations to protect and meet the needs of its citizens during conflict, in line with the theory of